Estimation of Anti-SARS-CoV-2 IgM/IgG Seroprevalence Among Non-Vaccinated and Vaccinated University Students: A Cross-Sectional Egyptian Study - Taha, Ahmed E.; Amer, Ibrahim; Sharawy, Shimaa El; Ghazy, Amany A. (Viruses, 2025)
It is essential to comprehend the humoral immune response to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and its vaccines to maximize the effectiveness of anti-SARSCoV-2 community immunization efforts. The aim of this cross-sectional study was to determine the seroprevalence of anti-SARS-CoV-2 IgM/IgG among newcomer students at Kafr Elsheikh University in Egypt, whether they had been vaccinated or not. Blood samples from 400 healthy newcomer students (200 non-vaccinated and 200 vaccinated) were evaluated for the presence of anti-SARS-CoV-2 IgM/IgG using colloidal gold immunochromatography lateral flow immunoassay cards, and then the results were confirmed by using specific ELISA tests. The prevalence of anti-SARS-CoV-2 antibodies among the participants (n = 400) was 56.3% for IgG and 13.3% for IgM. Regarding the non-vaccinated participants, 55.0% were females, the mean age was 18.2 years, and the mean BMI was 25.35. Regarding the vaccinated participants, 58.5% were females, the mean age was 18.1 years, and the mean BMI was 25.3. There were statistically non-significant correlations (p ˃ 0.05) between gender, BMI, and each of IgM- or IgG-positivity in both vaccinated and non-vaccinated groups. In total, 41.5% and 48.5% of the anti-SARS-CoV-2 IgM-positive and anti-SARS-CoV-2 IgG-positive participants were non-vaccinated, respectively. Furthermore, 58.5% and 51.5% of the anti-SARS-CoV-2 IgM-positive and anti-SARS-CoV-2 IgG-positive participants were vaccinated, respectively. No statistically significant association (p ˃ 0.05) in immunoglobulins positivity between the anti-SARS-CoV-2 non-vaccinated, and vaccinated groups. The anti-SARS-CoV-2 immunological response of nonsmokers, people who exercise regularly, and those who take vitamin supplements, eat a balanced diet, and use certain herbs is noteworthy. Among the vaccinated subjects, 96.6%, 25.0%, 31.9%, 45.7%, and 7.8% of the IgG-positive group, versus 97.2%, 60.6%, 64.2%, 52.3%, and 6.4% of the IgG-positive non-vaccinated group, were nonsmokers, exercisers, and those taking vitamin supplements, eating a balanced diet, and using herbs, respectively. Furthermore, 93.5%, 32.3%, 35.5%, 48.4%, and 6.5% of the IgM-positive vaccinated group, versus 100.0%, 63.6%, 81.8%, 45.5%, and 4.5% of the IgM-positive non-vaccinated participants, were nonsmokers, physical exercisers, vitamin supplement users, balanced eaters, and herbalists, respectively. Persons who are free from comorbidities, young, non-obese, non-smokers, engage in physical exercise, take vitamins, eat a balanced diet, and use certain immunostimulant herbal supplements, all have a strong anti-SARS-CoV-2 humoral immune response, even if they were not vaccinated. During pandemics, vaccination of this group should not be a priority to preserve vaccine doses for high-risk vulnerable people. Even if there is a lockdown during an anticipated future epidemic or pandemic, we should prioritize healthy eating and lifestyle choices, along with increasing physical activity.